2009
DOI: 10.1002/jmri.21731
|View full text |Cite
|
Sign up to set email alerts
|

MRI and histological analysis of beta‐amyloid plaques in both human Alzheimer's disease and APP/PS1 transgenic mice

Abstract: Purpose: To investigate the relationship between MR image contrast associated with beta-amyloid (A␤) plaques and their histology and compare the histopathological basis of image contrast and the relaxation mechanism associated with A␤ plaques in human Alzheimer's disease (AD) and transgenic APP/PS1 mouse tissues. Materials and Methods:With the aid of the previously developed histological coil, T* 2 -weighted images and R* 2 parametric maps were directly compared with histology stains acquired from the same set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 55 publications
8
148
1
Order By: Relevance
“…Similar patterns have been described in studies of AD transgenic mice and postmortem human AD cases, and were attributed to the presence of amyloid plaques using histological confirmation [11][12][13][14][15][16][17][18][19]. It has been proposed that the visualization on MRI of plaques in humans and mice is based on the fact that these deposits colocalize with iron, which gives rise to magnetic susceptibility effects on T2*-weighted images over volumes that are much larger than the actual size of amyloid plaques [17,[19][20][21][22][23][24]. An alternative method to measure these susceptibility changes in the brain is to measure the relative phase in regions of interest (ROIs), because it has been shown that this is a reliable indicator of the iron content in the brain [25][26][27][28].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar patterns have been described in studies of AD transgenic mice and postmortem human AD cases, and were attributed to the presence of amyloid plaques using histological confirmation [11][12][13][14][15][16][17][18][19]. It has been proposed that the visualization on MRI of plaques in humans and mice is based on the fact that these deposits colocalize with iron, which gives rise to magnetic susceptibility effects on T2*-weighted images over volumes that are much larger than the actual size of amyloid plaques [17,[19][20][21][22][23][24]. An alternative method to measure these susceptibility changes in the brain is to measure the relative phase in regions of interest (ROIs), because it has been shown that this is a reliable indicator of the iron content in the brain [25][26][27][28].…”
Section: Introductionsupporting
confidence: 78%
“…These features included hypointense foci and diffuse granular patterns of less distinct hypointense foci in the cerebral cortex [10]. Similar patterns have been described in studies of AD transgenic mice and postmortem human AD cases, and were attributed to the presence of amyloid plaques using histological confirmation [11][12][13][14][15][16][17][18][19]. It has been proposed that the visualization on MRI of plaques in humans and mice is based on the fact that these deposits colocalize with iron, which gives rise to magnetic susceptibility effects on T2*-weighted images over volumes that are much larger than the actual size of amyloid plaques [17,[19][20][21][22][23][24].…”
Section: Introductionsupporting
confidence: 61%
“…Earlier studies showed plaques using this method on 60-to 100-µm free-floating sections (LeVine 1997;Meadowcroft et al 2009) and iron-containing microglia in multiple sclerosis brains (LeVine 1997). No results of iron in layers IV/V have been reported using this method.…”
Section: Discussionmentioning
confidence: 90%
“…Iron elevation in AD brains, first demonstrated in 1953 [99], is a consistently reported finding [99][100][101][102][103][104][105][106][107][108]. Neuronal iron deposition causes oxidative stress via the Fenton reaction, which might contribute to elevated oxidative stress observed in the AD brain [109].…”
Section: Ironmentioning
confidence: 97%